2017
DOI: 10.1063/1.4974530
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of impurity-enhanced vacancy formation in metals

Abstract: Hydrogen induced vacancy formation in metals and metal alloys has been of great interest during the past couple of decades. The main reason for this phenomenon, often referred to as the superabundant vacancy formation, is the lowering of vacancy formation energy due to the trapping of hydrogen. By means of thermodynamics, we study the equilibrium vacancy formation in fcc metals (Pd, Ni, Co, and Fe) in correlation with the H amounts. The results of this study are compared and found to be in good agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The CoCrFeMnNi alloy was only measured up to 1,273 K because of greater volatilization of Mn. Per Bukonte et al .’s derivation 32 , the Gibbs free-energy change per mole in a metallic system subjected to vacancy formation iswhere ΔG , ΔH , ΔS conf , and ΔS vib are the Gibbs free energy change at temperature T , the formation enthalpy of vacancy, the configurational entropy of vacancy, and the vibrational entropy of vacancy, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CoCrFeMnNi alloy was only measured up to 1,273 K because of greater volatilization of Mn. Per Bukonte et al .’s derivation 32 , the Gibbs free-energy change per mole in a metallic system subjected to vacancy formation iswhere ΔG , ΔH , ΔS conf , and ΔS vib are the Gibbs free energy change at temperature T , the formation enthalpy of vacancy, the configurational entropy of vacancy, and the vibrational entropy of vacancy, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since there are size differences among the vacancies and different elements in HEAs, divacancy may form in alloys subjected to heating. Bukonte et al .’s thermodynamics derivations 32 focus on the effect of divacancy. In their derivations 32 , the total entropy term ΔS consists of the vibrational entropy ΔS vib and the configurational entropy ΔS conf .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowering of vacancy formation energy by hydrogen trapping is the origin of the superabundant vacancy effect discovered by Fukai andŌkuma [13]. Trapping by vacancies and the superabundant vacancy effect have been investigated by many authors since, for a wide range of metals [14][15][16][17][18][19][20][21][22]. This formation energy lowering was described by Kirchhheim [15,16] as a 'defactant' effect, by analogy with Gibbs' original theory of surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Even higher molar fractions for fcc Fe have been reported by Nazarov et al 22 However, Fe, Ni, and Pd have a much higher H solubility compared to Cu. 23 Furthermore, vacancies in these metals reach molar fractions of 10 −3 , 24 whereas in Cu, vacancy molar fractions are estimated to be one order of magnitude lower, even at high temperatures near the melting point. 25 Experimental studies for ECD Cu have revealed H molar fractions of around 10 −4 near the melting temperature of Cu under extreme H partial pressures exceeding 10 kbar (1 GPa).…”
Section: Introductionmentioning
confidence: 99%